Status Hukum Tanah Warga Yang Bermukim Di Wilayah Pesisir Perbatasan Kabupaten Nunukan Provinsi Kalimantan Utara - Sulaiman, Sulaiman; Makka, Zulvia (JATISWARA, 2018)
The province of North Kalimantan is the youngest province in Indonesia, located in the northern part of Kalimantan Island. Northern Kalimantan Province is established based on Law No. 20 of 2012 establishing the Northern Kalimantan Province. Nunukan Regency is one of five districts / cities in the province of North Kalimantan covering an area of ​​14,263.68 km2. Geographically, Nunukan Regency is located in the northernmost region of Kalimantan, which borders directly with a neighboring country, Sabah-Malaysia. The legal status of the land becomes a written proof that is legally recognized. All land rights are recorded in the form of National Land Agency (BPN) certificates. BPN creates duplicates of landowners to avoid future risks, such as: B.: Lost certificates, burned certificates and duplicate certificates. In Indonesia, land ownership status is governed by the Basic Law of Agriculture (UUPA) No. 5 of 1960 on Agricultural Principles. Rural residents living in the Border Coast, especially in the Nunukan Subdistrict, Nunukan Utara district, is the Nunukan Regency, a leased land owned by PT. Inhutani as the de facto landlord (HGU), above the property for PT. Inhutani in the Nunukan district, Nunukan district, Nunukan Utara district stands thousands of buildings owned by both the community and the government, where the majority have no legal proof of domination. The problem in this study is the legal status of the ownership of land in the border coastal areas and the policy of the local government in providing legal solutions to control the use of land in coastal areas. Based on the results that concludes the legal status of the land of coastal residents who live in the region as the right boundary, as the conversion of Hak Guna Usaha (HGU) by PT.Inhutani is used, that researchers know ended Hak Guna Usaha ( HGU) was on the ground since 2009. But it was extended to 2038. While the legal solution for providing legal certainty of the owner of the building in the country of PT. Inhutani receives until the bleaching of the rights building use rights (HGB) to the community, because PT. Inhutani is no longer productive / operates and produces forest products, in Nunukan sub-district, Nunukan Utara village, but only the establishment of settlements and thousands of municipal and state buildings.